Double drainage of total anomalous pulmonary venous connection: A rare variant of mixed total anomalous pulmonary venous connection - Mani Ram Krishna; Ganesh Kumar Gnanappa; Jonathan Mervis; Jonathan Forsey; Julian Ganesh Ayer; Yishay Orr (Wolters Kluwer Medknow Publications, 2020)
Total Anomalous Pulmonary Venous Connection (TAPVC) is frequently classified based on the system proposed by Craig, Darling and Rothney. Occasionally variants are reported which do not fit into these classic forms. One such variant is the double drainage of TAPVC where the confluence has connections at two different levels. We report two infants with a double drainage pattern of TAPVC